SUSPENSION OF EMPLOYMENT CONTRACT: ANALYSIS OF COURT PRACTOCE - Garashchenko, Liudmyla (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Purpose: to outline the main issues that arise when applying legislature regarding the suspension of employment contracts based on the analysis of court practice. Research methods: to achieve the research goal, methods of synthesis, analysis, generalization, comparison, forecasting, dialectical and others were used. Results: the analysis of court practice indicates that in cases where no violations of employees’ labour rights by employers were established, the absolute impossibility for employer to provide work were, in particular: hostilities taking place directly in the area (locality) of the enterprise, proximity of the enterprise to a combat zone, missile strikes. In these cases, the employer temporarily suspended the employment contracts with virtually all employees (rather than one or a few) who had an employment relationship with the employer. Absolute impossibility to provide and thus to perform work is also evidenced by circumstances such as: destruction as a result of hostilities of necessary production, organisational, technical capabilities, production facilities essential for performing work, or the impossibility of their functioning through objective reasons not dependent on the employer; the inability to transfer an employee to another job or involve him in remote work. The practice of the Supreme Court regarding the application of Article 235 of the Labour Code of Ukraine concerning the compensation of average wages during forced absenteeism in the cases of suspension of the employment contract has been analysed. Discussion: under the conditions of martial law, the Code does not provide for a mechanism for compensation (lost wages) from the aggressor state. Similarly, the norms of the Labour Code do not envisage a corresponding compensation mechanism in cases of abuse by the employer of the norms of Article 13 of Code № 2136-IX. By applying the analogy of the law, the court, establishing the employer’s guilt in the unlawful suspension of the employment contract, awarded the average monthly wage for forced absenteeism based on parts 1 and 2 of Article 235 of the Labour Code of Ukraine.